Une balle blanche dans un roman noir - Sophie Vallas (Transatlantica)
In 1982 Paul Auster published a roman noir entitled Squeeze Play under the pseudonym of Paul Benjamin. The novel is also a “baseball novel”: its plot essentially deals with a baseball New York team and its former, fallen star, and the final resolution of the mystery intervenes thanks to a revelation brought by a baseball game in which a rather rare and spectacular maneuver (the double suicide squeeze) is used by one of the teams to turn the tables and win the game. This paper analyzes the place of baseball in Squeeze Play: it first appears as an essential element in the very structure of the plot, but it is also, for Auster, a way of questioning the myth of the hero in an American society whose main aspects (sports, politics, private life) are eaten up by corruption and perversion. The links Auster establishes between roman noir and baseball novel are also dealt with.